Reactive oxygen species and p38 mitogen-activated protein kinase mediate tumor necrosis factor α-converting enzyme (TACE/ADAM-17) activation in primary human monocytes. - Scott, A; O'Dea, K; O'Callaghan, D; Williams, L; Dokpesi, J; Tatton, L; Handy, J; Hogg, P; Takata, M (2011)
Tumor necrosis factor α-converting enzyme (TACE) is responsible for the shedding of cell surface TNF. Studies suggest that reactive oxygen species (ROS) mediate up-regulation of TACE activity by direct oxidization or modification of the protein. However, these investigations have been largely based upon nonphysiological stimulation of promonocytic cell lines which may respond and process TACE differently from primary cells. Furthermore, investigators have relied upon TACE substrate shedding as a surrogate for activity quantification. We addressed these concerns, employing a direct, cell-based fluorometric assay to investigate the regulation of TACE catalytic activity on freshly isolated primary human monocytes during LPS stimulation. We hypothesized that ROS mediate up-regulation of TACE activity indirectly, by activation of intracellular signaling pathways. LPS up-regulated TACE activity rapidly (within 30 min) without changing cell surface TACE expression. Scavenging of ROS or inhibiting their production by flavoprotein oxidoreductases significantly attenuated LPS-induced TACE activity up-regulation. Exogenous ROS (H(2)O(2)) also up-regulated TACE activity with similar kinetics and magnitude as LPS. H(2)O(2)- and LPS-induced TACE activity up-regulation were effectively abolished by a variety of selective p38 MAPK inhibitors. Activation of p38 was redox-sensitive as H(2)O(2) caused p38 phosphorylation, and ROS scavenging significantly reduced LPS-induced phospho-p38 expression. Inhibition of the p38 substrate, MAPK-activated protein kinase 2, completely attenuated TACE activity up-regulation, whereas inhibition of ERK had little effect. Lastly, inhibition of cell surface oxidoreductases prevented TACE activity up-regulation distal to p38 activation. In conclusion, our data indicate that in primary human monocytes, ROS mediate LPS-induced up-regulation of TACE activity indirectly through activation of the p38 signaling pathway.